Oligogalacturonides as an alternative to increase nitrogenous nutrition and growth in common bean (Phaseolus vulgaris L.) - Lara-Acosta, Danurys (2023)
Introduction. Bean production is limited by the availability of nitrogen in the soil and its low efficiency in biological nitrogen fixation. The application of a bio-stimulant based on oligogalacturonides (Pectimorf®) is considered an alternative to improve nitrogen nutrition in early stages of growth, but its effectiveness in later stages of cultivation is unknown. Objective. To determine the effect of Pectimorf® on indicators related to biological nitrogen fixation and the growth of common bean plants bio-fertilized with Azofert®-F during the R5 growth stage (pre-flowering). Materials and methods. The research was carried out at the Genomic Sciences Center of the Universidad Nacional Autónoma de México (October 2018-March 2019) and at the Instituto Nacional de Ciencias Agrícolas en Cuba (November-December 2019). Experiments were carried out under controlled and semi-controlled conditions, evaluating the application of 10 mg L-1 of Pectimorf® to seeds along with Azofert®-F and foliar spraying at 5 and 100 mg L-1 on bio-fertilized plants. Plants treated only with Azofert® were used as a control. Nodulation, indicators of biological nitrogen fixation, and plant growth were evaluated. Results. Under controlled conditions, Pectimorf® stimulated nodulation, root development, and increased nitrogenase activity. In the semi-controlled conditions, it favored nodulation and growth, with the seed treatment and foliar spraying (100 mg L-1) standing out. Pectimorf® also increased the ureides synthesis in the nodules and the nitrogen content in the leaves. This product showed more than a 15 % effectiveness in relation to bio-fertilization. Conclusions. The application of Pectimorf® improved biological nitrogen fixation and growth during pre-flowering stage of common bean.